2013
DOI: 10.1002/pssa.201329282
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of NV centers in nano‐ and ultrananocrystalline diamond pillars

Abstract: Diamond nanopillars with diameters of 1 mm down to 50 nm have been fabricated from two types of diamond thin films, namely nanocrystalline diamond (NCD) and ultrananocrystalline diamond (UNCD) using electron beam lithography (EBL) and reactive ion etching (RIE) in an inductively coupled oxygen plasma (ICP). Aim of the study was to investigate the suitability of these pillars to incorporate nitrogen-vacancy (NV) color centers for applications in quantum information technology (QIT). The first part of the invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
(55 reference statements)
1
11
1
Order By: Relevance
“…The pillars at the edge of an array were slightly stronger etched than the pillars surrounding the center, which can be seen by comparing their sidewalls in Figure . Those at the edge were more tapered, however this effect is far less pronounced compared to a previous study, where we investigated single nanopillars separated by five micrometers and the top diameters were significantly smaller than the bottom ones showing pronounced tapering. This could be explained by the higher package density of the pillars in the current study: Their overall exposure to the plasma in the ICP RIE step is limited which reduces overetching and mask erosion.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…The pillars at the edge of an array were slightly stronger etched than the pillars surrounding the center, which can be seen by comparing their sidewalls in Figure . Those at the edge were more tapered, however this effect is far less pronounced compared to a previous study, where we investigated single nanopillars separated by five micrometers and the top diameters were significantly smaller than the bottom ones showing pronounced tapering. This could be explained by the higher package density of the pillars in the current study: Their overall exposure to the plasma in the ICP RIE step is limited which reduces overetching and mask erosion.…”
Section: Resultscontrasting
confidence: 73%
“…ii) in situ doping during the diamond growth by introducing precursor gas mixtures into the reaction chamber, e.g. Si containing gases like SiH 4 for the creation of SiV centers or nitrogen gas for the formation of NV centers: either in a controlled way for nanometer‐precision depth control of the generated NV centers (delta‐doping) or distributed within the diamond film by a background pressure of nitrogen in the chamber . In the case of SiV centers, also solid precursor sources are possible, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the deposition of a 100 nm chromium layer and a standard lift‐off process, a circular‐shaped chromium mask array was formed. Then, a short ICP etching stage (for 1/2 min) was performed with oxygen plasma for the nanopillar fabrication (200 nm high pillars) applying process parameters (1000 W ICP power, 200 W radio frequency (RF) power, 10 sccm O 2 flow, and 5 mTorr {0.7 Pa} working pressure) optimized in a previous work . After the formation of the nanopillar arrays, the chromium mask was removed using chromium etchant (Figure a of the EDS measurement clearly demonstrated that the chromium mask was successfully removed from the pillar apex).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally to that, rectangular marker structures were written in each row nearby the 50 nm pillars to make localization of these small structures easier. For the development of the structures a mixture of methyl isobutyl ketone (MIBK) and IPA 1:3 was applied for 165 s followed by a cleaning step in IPA for 30 s …”
Section: Methodsmentioning
confidence: 99%